INFLAMMATORY COMPLICATIONS ASSOCIATED WITH INTRAUTERINE DEVICE USE (European Journal of Interdisciplinary Research and Development, 2025)
Background: Intrauterine devices (IUDs) are among the most effective and widely used long-acting reversible contraceptive methods worldwide. Despite their high efficacy and overall safety, inflammatory complications may develop in certain clinical situations. Objective: To analyze the etiology, risk factors, pathogenesis, and clinical features of inflammatory complications associated with intrauterine device use. Materials and Methods: A narrative review of international scientific literature was conducted using data from PubMed, WHO guidelines, and peer-reviewed gynecological journals published between 2000 and 2024. Results: The development of inflammatory complications is primarily associated with pre-existing genital tract infections, нарушение aseptic techniques during IUD insertion, multiple sexual partners, and early postpartum or post-abortion insertion. The highest risk period is within the first 20 days after insertion. Conclusion: Intrauterine devices remain a safe and effective contraceptive method. Careful patient selection, screening for sexually transmitted infections, and strict adherence to international clinical guidelines significantly reduce the risk of inflammatory complications.